Thermal, morphological, and biodegradability properties of bioplastic fertilizer composites made of oil palm biomass, fertilizer, and poly(hydroxybutyrate-co-valerate) - Ahmad Saffian, Harmaen; Abdan, Khalina; Hassan, Mohd Ali; Ibrahim, Nor Azowa (Hindawi Publishing Corporation, 2016)
Slow-release bioplastic fertilizer (BpF) composites were developed by processing oil palm empty fruit bunch (EFB), fertilizer, and poly(hydroxybutyrate-co-valerate) (PHBv) using extrusion techniques with controlled formulation and temperature. The temperature was kept at 150°C for 3 to 5 min during processing using twin-screw extruder. The PHBv lost weight gradually with the increasing temperature and its thermal degradation occurred initially at 263.4°C and reached the maximum at 300.7°C. Scanning electron microscope (SEM) images showed that the bonding of all composites created small gaps between matrices polymer and fiber because the hydrophilic characteristic of EFB fibers weakened the interfacial bonding. PHBv/EFB/NPKC2 showed faster biodegradation over PHBv/NPKC1 and PHBv/NPKC2, which was 99.35% compared to 68.66% and 90.28%, respectively.